La Basilica Aemilia e il lato settentrionale del Foro Romano dalla media repubblica al primo impero - Bruni, Valerio (Römische Mitteilungen, 2024)
This paper analyses the Basilica Aemilia, a building that has garnered the attention of many scholars, especially in recent times, regarding its construction history and architectural articulation. The inspiration for our study was provided by the opportunity to examine previously unpublished archival documentation of the 20th-century excavation. These are both descriptive (notes by Torquato Ciacchi and Gustavo Tognetti) and graphic (drawings by Tognetti and Luigi de Cosa), and also include the elaborations of these materials previously conducted by Heinrich Bauer in preparation for a volume on the basilica, which, due to his premature death, was never published.